FIQIH MUAMALAH DAN FIQIH LINGKUNGAN DALAM MENJAWAB TANTANGAN EKONOMI DIGITAL DAN PELESTARIAN ALAM - Rahmad, Rahmad (Jurnal Tahqiqa : Jurnal Pemikiran Hukum Islam, 2025)
The development of the digital economy provides opportunities and challenges in the context of muamalah fiqh and environmental preservation. This research aims to explore the contribution of muamalah fiqh in facing the dynamics of the digital economy and supporting nature conservation. Using a qualitative approach based on literature study, analysis was carried out on the relationship between the principles of muamalah fiqh and digital economic and environmental issues. The results show that muamalah fiqh provides ethical guidance in digital transactions and encourages ecological responsibility through the principles of maqashid sharia.